Pendampingan Kajian Revisi Peraturan Menteri Komunikasi Dan Informatika Nomor 22 Tahun 2013 - Sri Dewi Anggadini; Tenri Haeriyah; Mega Silvia (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2021)
The purpose of this community service activity is to assist in the study of the revision of the text of the Minister of Communication and Informatics Regulation regarding the implementation of Universal Postal Services in accordance with the Act. In addition to these objectives, it also includes a draft regulatory text that includes the following criteria: mechanism, program planning, monitoring, supervision, verification and evaluation so as to create an accountable LPU implementation. The method of community service activities is carried out descriptively with a survey approach to several locations for the Universal Postal Service, through several stages including: preparation, collection of related data and information, data processing and analysis, preparation of technical recommendations as well as discussions, socialization and recommendations. In the implementation process, activities are carried out starting from collecting field verification data and documents, data processing and analysis, as well as compiling PM LPU revisions. The PKM activities carried out provide benefits in the form of producing a text of the Minister of Communication and Informatics Regulation on the implementation of Universal Postal Services that is in line with the Law. Through the implementation of PKM, it is hoped that the postal administration is in accordance with the expectations and needs of the community, the Government needs to take concrete and quite populist steps to support the postal administration to be carried out properly, effectively, efficiently and accountably, including the need to provide guidance and protection for postal operators, determine requirements strict rules for the feasibility of postal operators, guarantees for the reliability of products and types of postal services, preventing monopolistic practices in postal administration and community participation in postal operations.